Early Postnatal Development of Somastostatinergic Systems in Brainstem Respiratory Network - Llona-Rodriguez, I; Troc-Gajardo, J (Springer New York LLC, 2017)
Somatostatin is a peptide able to stop breathing, acting in the neural network that generates and control the respiratory rhythm. In this chapter, we present data on the early postnatal development of somatostatinergic systems in the mouse brainstem and summarize evidence for their influence on the generation and control of the respiratory rhythm. © Springer International Publishing AG 2017.